Subject‐driven titration of biphasic insulin aspart 30 twice daily is non‐inferior to investigator‐driven titration in Chinese patients with type 2 diabetes inadequately controlled with premixed human insulin: A randomized, open‐label, parallel‐group, multicenter trial. Issue 1 (25th May 2015) - Yang, Wenying; Zhu, Lvyun; Meng, Bangzhu; Liu, Yu; Wang, Wenhui; Ye, Shandong; Sun, Li; Miao, Heng; Guo, Lian; Wang, Zhanjian; Lv, Xiaofeng; Li, Quanmin; et al.
Abstract: Aims/Introduction: The present study was to compare the efficacy and safety of subject‐driven and investigator‐driven titration of biphasic insulin aspart 30 (BIAsp 30) twice daily (BID). Materials and Methods: In this 20‐week, randomized, open‐label, two‐group parallel, multicenter trial, Chinese patients with type 2 diabetes inadequately controlled by premixed/self‐mixed human insulin were randomized 1:1 to subject‐driven or investigator‐driven titration of BIAsp 30 BID, in combination with metformin and/or α‐glucosidase inhibitors. Dose adjustment was decided by patients in the subject‐driven group after training, and by investigators in the investigator‐driven group. Results: Eligible adults ( n = 344) were randomized in the study. The estimated glycated hemoglobin (HbA1c ) reduction was 14.5 mmol/mol (1.33%) in the subject‐driven group and 14.3 mmol/mol (1.31%) in the investigator‐driven group. Non‐inferiority of subject‐titration vs investigator‐titration in reducing HbA1c was confirmed, with estimated treatment difference −0.26 mmol/mol (95% confidence interval −2.05, 1.53) (–0.02%, 95% confidence interval –0.19, 0.14). Fasting plasma glucose, postprandial glucose increment and self‐measured plasma glucose were improved in both groups without statistically significant differences. One severe hypoglycemic event was experienced by one subject in each group. A similar rate of nocturnal hypoglycemia (events/patient‐year) was reported in the subject‐driven (1.10) and investigator‐driven (1.32) groups. There were 64.5 and 58.1% patients achieving HbA1c <53.0 mmol/mol (7.0%), and 51.2 and 45.9% patients achieving the HbA1c target without confirmed hypoglycemia throughout the trial in the subject‐driven and investigator‐driven groups, respectively. Conclusions: Subject‐titration of BIAsp 30 BID was as efficacious and well‐tolerated as investigator‐titration. The present study supported patients to self‐titrate BIAsp 30 BID under physicians' supervision. Abstract : This research was a head‐to‐head comparison with patient‐titration and investigator‐titration of a premixed formulation BIAsp 30 BID in Chinese population, providing evidences that patient‐driven titration was as efficacious and safe as investigator‐driven titration. The data are important for both patients who are insufficiently involved in self‐management of their conditions, and caregivers who are considering empowering patients.